Ulysses - Joyce, James 1882-1941 (London Penguin, 1960)
Ulysses chronicles the appointments and encounters of the itinerant Leopold Bloom in Dublin in the course of an ordinary day, 16 June 1904. Ulysses is the Latinised name of Odysseus, the hero of Homer's epic poem the Odyssey, and the novel establishes a series of parallels between the poem and the novel, with structural correspondences between the characters and experiences of Bloom and Odysseus, Molly Bloom and Penelope, and Stephen Dedalus and Telemachus, in addition to events and themes of the early 20th-century context of modernism, Dublin, and Ireland's relationship to Britain. The novel is highly allusive and also imitates the styles of different periods of English literature.
'Ulysses' is considered one of the most important works of modernist literature and has been called "a demonstration and summation of the entire movement." According to Declan Kiberd, "Before Joyce, no writer of fiction had so foregrounded the process of thinking".
Originally published in 1922
Keywords: 20th Century (1901-2000); Novel